Great risk insurances and disproportionate protection of insured persons in insurance contract Law - Corzo de la Colina, Rafael (2017)
In this article, the authors tell us about great risk insurances and describe its regulation in foreign law. Then, they point out the protective role of State in the consumption relationship is to reduce information asymmetries, but there is no total disclosure obligation in the market. Therefore, information asymmetry ceases to be relevant when the user of the service has negotiating capacity and necessary resources to make an informed decision. They conclude it is pertinent to equate the application of the Peruvian Insurance Contract Law to international standards.